Effect of thermo-mechanical controlled process on microstructural texture and hydrogen embrittlement resistance of API 5L X70 pipeline steels in sour environments. (1st December 2021) - Pourazizi, Reza; Mohtadi-Bonab, M.A.; Zadeh Davani, Reza Khatib; Szpunar, J.A.
Abstract: Two different thermo-mechanical controlled process procedures were utilized to modify the microstructure and texture of pipeline steel. Moreover, electrochemical hydrogen charging and hydrogen permeation experiments were used to investigate the effect of texture and microstructure on the HIC susceptibility of tested specimens. The results showed that different used TMCP parameters did not change the microstructure of the tested specimens significantly. It was also concluded that the higher number of reduction steps led to the generation of smaller grains with the same total reduction percentage. The cooling rate was another factor affecting the grain size in which a higher cooling rate resulted in smaller grain size. The hydrogen charging results illustrated that the increase of the grain size led to better resistance of the steel to the HIC cracking. It was observed that the specimen containing a higher density of reversible traps seems to be more susceptible to HIC cracking. Highlights: Different TMCP procedures were used to modify the microstructure of pipeline steel. TMCP parameters did not change the microstructure of specimens significantly. TMCP parameters generated different grain sizes elongated along rolling direction. An increase of the grain size led to better resistance of the steel to the HIC. Specimen with a higher density of reversible traps is more susceptible to HIC.